Nonlinear Fiscal Multiplier: Evidence From Portugal - Gonçalves, T.; Mendes, V.; Mendes, D. A. (3rd International Conference on Dynamics, Games and Science, 2014)
This paper aims to analyze the existence of nonlinearities on the Portuguese Fiscal Multiplier. The main goal is to test if symmetric fiscal shocks have asymmetric effects depending on the business cycle position. In order to do so, will be followed the recent literature of Auerbach & Gorodnichenko which implies an application of a STVAR model to Portuguese macroeconomic and fiscal variables.